PENGARUH KUALITAS PELAYANAN DAN POTONGAN HARGA TERHADAP KEPUASAN PELANGGAN - Mardiyana Mardiyana; Hartanti Nugrahaningsih; Leny Muniroh (Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine the eflect of service quality, price discounts on customer satisfaction at PTManufaktur Indonesia Bogor Management. The method used is library research, and field research with a questionnaire. The study was conducted with training participants, namely a population of 500 participants, a sample of 85 participants. Service quality sales regression Y = 2.667 + 0.331X1,. The hypothesis test obtained by the value of t count > t table or (9.904 > 1.988). Thus H0 is rejected and Ha1 is accepted, this shows that there is a significant influence between service quality and customer satisfaction. Discounts obtained by the value of the regression equation Y = 2.396 + 1.237X2. Hypothesis test obtained t count > t table or (31.076 > 1.988). Thus, H0 is rejected and Ha2 is accepted, this shows that there is a significant eflect between price discounts on customer satisfaction. Based on the results of the research, it shows that service quality (X1) and price discounts (X2) have a significant eflect on customer satisfaction by obtaining a regression equation Y = 2.396 + 0.202 X1 + 0.310 X2 by obtaining a deduction coefficient value or a simultaneous influence contribution of 93.4%. while the remaining 6.6% is influenced by other variables that were not carried out in this study, including price, promotion, purchasing decision variables. The correlation coefficient is R = 0.966 this shows that it has a positive relationship. The hypothesis test obtained the calculated F value > Ftabeil or (580.758 > 2.716). Thus, H0 is rejected and Ha3 is accepted, this shows that there is a simultaneous significant eflect between service quality and price discounts on customer satisfaction at PT. Manufacturing Management Indonesia Bogor.